How Does Religion Affect Giving to Outgroups and Secular Organizations? A Systematic Literature Review - Kidist Ibrie Yasin; Anita Graeser Adams; David P. King (Religions, 2020)
Although religious giving represents the largest sector of charitable giving in the US, its overall impact on social welfare has been questioned, pointing to the possibility that the majority of funding might stay within the religious community, with little benefit to outgroups or secular charity. Despite multiple studies showing a positive relationship between religion and secular and outgroup giving, some empirical findings show a negative or non-significant relationship. By employing a systematic literature review, the current study explores theories and empirical evidence to provide an integrative framework that identifies the mechanisms and directions through which religion affects giving to outgroups and secular organizations. The study also compares the major five religious traditions and giving to outgroups and secular organizations. The study finds that religious teachings, norms, values, social network, and private rituals, determine the direction of the relationship between religion and giving to outgroups and secular organizations. The study concludes that, despite the dominant positive relationship between religion and giving to outgroup and secular organizations, there remains heterogeneity among the studies based on their location, operationalization of religion and secular giving, and methodology used. The study also poses some implication questions and points out future research directions.